The influence of dietary carbohydrate on perceived recovery status differs at the group and individual level—Evidence of nonergodicity among endurance athletes - Rothschild, J. A.; Stewart, T.; Kilding, A. E.; Plews, D. J. (Journal of Science in Sport and Exercise, 2024)
Purpose Research findings are typically reported at the group level but applied to individuals. However, an emerging issue in sports science concerns nonergodicity—whereby group-level data cannot be generalized to individuals. The purpose of this study was to determine if the relationship between daily carbohydrate intake and perceived recovery status displays nonergodicity.